Windows developer power tools - Avery, James (O'Reilly, 2006)
Software developers need to work harder and harder to bring value to their development process in order to build high quality applications and remain competitive. Developers can accomplish this by improving their productivity, quickly solving problems, and writing better code. A wealth of open source and free software tools are available for developers who want to improve the way they create, build, deploy, and use software. Tools, components, and frameworks exist to help developers at every point in the development process. Windows Developer Power Tools offers an encyclopedic guide to m.